RMS-R3 – the system for monitoring the region of interactions and background at the LHCB experiment (CERN) - S. B. Chernyshenko; V. M. Dobishuk; O. Yu. Okhrimenko; F. Alessio; H. Schindler; V. O. Kyva; V. M. Pugatch; G. Corti (Ядерна фізика та енергетика)
The upgraded Large Hadron Collider beauty (LHCb) detector will provide data taken in Run3 at the instantaneous luminosity of proton-proton collisions increased to 2⋅1033 cm-2s-1 at energies of up to 14 TeV. To ensure the safe operation of the experiment, a new beam and background Radiation Monitoring System (RMS-R3) was built. RMS-R3 is based on metal-foil detector technology developed at the Institute for Nuclear Research, National Academy of Sciences of Ukraine (Kyiv, Ukraine). The system comprises four detector modules with two sensors in each. Their frequency response is proportional to the flux of incident charged particles. The modules are located around the beam pipe at a distance of 2.2 m from the interaction point. The results measured during the Run3 in 2022 testify to the reliable operation of the system. Applying the asymmetry method, high-accuracy data were obtained on the localization of the interactions region and the beam and background contribution.